A Brief Review Of Articles Published On The Results Of Certain Scientific Studies Dedicated To The Application Of Silver Nanoparticles In Medicine And Pharmacy. (Texas Journal of Medical Science, 2026)
In recent years, nanotechnology has become one of the key driving forces in the advancement of modern medicine, leading to increased interest in the study of silver nanoparticles and the expansion of their practical applications. Owing to their pronounced antibacterial and antiseptic properties, silver nanoparticles are increasingly used in medical and pharmaceutical practice. This article presents a brief analytical review of scientific studies published in recent years in the global scientific literature, focusing on the application of silver nanoparticles in medicine and pharmacy.